Using MRI to study the alterations in liver blood flow, perfusion, and oxygenation in response to physiological stress challenges: Meal, hyperoxia, and hypercapnia. Issue 6 (24th October 2018) - Cox, Eleanor F.; Palaniyappan, Naaventhan; Aithal, Guruprasad P.; Guha, I. Neil; Francis, Susan T.
Abstract : Background: Noninvasive assessment of dynamic changes in liver blood flow, perfusion, and oxygenation using MRI may allow detection of subtle hemodynamic alterations in cirrhosis. Purpose: To assess the feasibility of measuring dynamic liver blood flow, perfusion, and T2 * alterations in response to meal, hypercapnia, and hyperoxia challenges. Study Type: Prospective. Subjects: Ten healthy volunteers (HV) and 10 patients with compensated cirrhosis (CC). Field Strength/Sequence: 3T; phase contrast, arterial spin labeling, and T 2 * mapping. Assessment: Dynamic changes in portal vein and hepatic artery blood flow (using phase contrast MRI), liver perfusion (using arterial spin labeling), and blood oxygenation ( T 2 * mapping) following a meal challenge (660 kcal), hyperoxia (target PET O2 of 500 mmHg), and hypercapnia (target increase PET CO2 of ∼6 mmHg). Statistical Tests: Tests between baseline and each challenge were performed using a paired two‐tailed t ‐test (parametric) or Wilcoxon‐signed‐ranks test (nonparametric). Repeatability and reproducibility were determined by the coefficient of variation (CoV). Results: Portal vein velocity increased following the meal (70 ± 9%, P < 0.001) and hypercapnic (7 (5–11)%, P  = 0.029) challenge, while hepatic artery flow decreased (–30 ± 18%, P  = 0.005) following the meal challenge in HV. In CC patients, portal vein velocity increased (37 ± 13%, P  = 0.012) without the decrease in hepatic artery flow following the meal. In both groups, the meal increased liver perfusion (HV: 82 ± 50%, P < 0.0001; CC: 27 (16–42)%, P  = 0.011) with faster arrival time of blood (HV: –54 (–56‐30)%, P  = 0.074; CC: –42 ± 32%, P  = 0.005). In HVs, T 2 * increased after the meal and in response to hyperoxia, with a decrease in hypercapnia (6 ± 8% P  = 0.052; 3 ± 5%, P  = 0.075; –5 ± 6%, P  = 0.073, respectively), but no change in CC patients. Baseline between‐session CoV <15% for blood flow and <10% for T 2 * measures. Data Conclusion: Dynamic changes in liver perfusion, blood flow, and oxygenation following a meal, hyperoxic, and hypercapnic challenges can be measured using noninvasive MRI and potentially be used to stratify patients with cirrhosis. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:1577–1586.